FAKTORSKA STRUKTURA I RELACIJE MOTORIČKIH I SUTUACIONO - MOTORIČKIH SPOSOBNOSTI RUKOMETAŠA - Saša Marković; Nenad Pivač (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The motor activity during a handball game is characterized by loads of great intensity and by large scope, which are structured as interval-variable loads. The subject of this research are manifest and latent structures (the presence and nature of the inter-relationship) of motor and situational-motor abilities of the 2nd league handball players before the beginning of the competitions. The main goal of this research is to ascertain the existing relation among the studied variables, as well as the belonging of tests to the factors they define. According to the subject and goals of the research, the related hypotheses have been formulated.The sample was made of the active handball players, competing in the 2nd league. It consisted of 105 players aged between 18-25. The variables for this research of defence cover and represent motor abilities (16 tests), as well as situational-motor abilities (5 tests) in order to obtain a more complex picture of the specific motor abilities distinctive for handball. The research methodology has been defined in accordance with the formulated hypotheses, the subject and the goal of the research. The obtained results have been presented as containing two parts, the area of general and the area of situational motorics, as well as their inter-relationship. After the presentation (text and tables), the conclusions have been drawn, pointing out the importance of the obtained results for the practice in working with handball players